COMMUNICATION STRATEGIES USED BY ELT STUDENTS ACROSS GENDERS - Yusparizal Yusparizal; Enny Irawati; Mirjam Anugerahwati (Jurnal Pendidikan Humaniora, 2018)
Abstract: This research investigated communication strategies used by female and male students of ELT at Universitas Negeri Malang and their perception on the use of communication strategies in oral communication. This research employed descriptive qualitative research design. It used purposeful sampling technique. It was found out that both female and male students only used 10 out of 12 communication strategies. Both male and female students perceived that communication strategies were helpful to cope with difficulties, to maintain the conversation, to negotiate meaning, to solve problems, and to enhance the effectiveness of communication.Key Words: communication strategies, across genders, ELT, Universitas Negeri MalangAbstrak: Penelitian ini mencari strategi komunikasi yang digunakan oleh mahasiswa pendidikan bahasa Inggris laki-laki dan perempuan di Universitas Negeri Malang dan persepsi mereka terhadap penggunaan strategi komunikasi tersebut dalam komunikasi lisan. Penelitian ini dilaksanakan dengan menggunakan desain penelitian deskriptif kualitatif. Penelitian ini menggunakan teknik purposive sampling. Dari penelitian ini, ditemukan bahwa baik mahasiswi maupun masiswa sama-sama hanya menggunakan 10 dari 12 strategi komunikasi. Para mahasiswi dan mahasiswa juga sama-sama setuju bahwa strategi komunikasi sangat membantu mereka dalam komunikasi lisan.Kata kunci: strategi komunikasi, lintas gender, pendidikan bahasa Inggris, Universitas Negeri Malang